2002
DOI: 10.1073/pnas.122067599
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite evolution inferred from human– chimpanzee genomic sequence alignments

Abstract: Most studies of microsatellite evolution utilize long, highly mutable loci, which are unrepresentative of the majority of simple repeats in the human genome. Here we use an unbiased sample of 2,467 microsatellite loci derived from alignments of 5.1 Mb of genomic sequence from human and chimpanzee to investigate the mutation process of tandemly repetitive DNA. The results indicate that the process of microsatellite evolution is highly heterogeneous, exhibiting differences between loci of different lengths and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
118
1
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(139 citation statements)
references
References 50 publications
18
118
1
2
Order By: Relevance
“…These subgenomes were delineated in humanorangutan-macaque BLASTZ alignments broken into nonoverlapping 1-Mb windows based on human coordinates. For nucleotides belonging to each subgenome in each window, we computed human-specific insertion and deletion rates, human-specific nucleotide substitution rates (using the Jukes-Cantor model) (55), and human-orangutan pairwise microsatellite mutability (56). The latter was obtained for mononucleotide microsatellites with ≥9 repeats that were sufficiently abundant per 1 Mb and for repeat number bins of size four-e.g., microsatellites with 9-12 repeats formed one bin, etc.…”
Section: Methodsmentioning
confidence: 99%
“…These subgenomes were delineated in humanorangutan-macaque BLASTZ alignments broken into nonoverlapping 1-Mb windows based on human coordinates. For nucleotides belonging to each subgenome in each window, we computed human-specific insertion and deletion rates, human-specific nucleotide substitution rates (using the Jukes-Cantor model) (55), and human-orangutan pairwise microsatellite mutability (56). The latter was obtained for mononucleotide microsatellites with ≥9 repeats that were sufficiently abundant per 1 Mb and for repeat number bins of size four-e.g., microsatellites with 9-12 repeats formed one bin, etc.…”
Section: Methodsmentioning
confidence: 99%
“…Despite accounting for this ascertainment bias, Cooper, Rubinsztein, and Amos [9] found that human dinucleotide microsatellites are significantly longer than their chimpanzee orthologues. Webster, Smith, and Ellegren [51] considered many more microsatellites and concurred with [9]'s findings. They also found that human mononucleotide microsatellites are more likely to be shorter than their chimpanzee counterparts.…”
Section: Experiments and Analysismentioning
confidence: 62%
“…The estimated parameters imply microsatellites shorter than eighteen repeat units have a bias towards expansions, while longer microsatellites have a bias towards contractions. When they relaxed the assumption that the same model parameters applied in both the human and chimpanzee lineages, they found that this focal length increased to twentyone repeats in humans while remaining at eighteen repeats in chimpanzees, further confirming the findings in [9] and [51].…”
Section: Experiments and Analysismentioning
confidence: 66%
See 2 more Smart Citations